2007
DOI: 10.1038/sj.bjc.6603949
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of epidermal growth factor receptor mutation status in serum DNA as a predictor of response to gefitinib (IRESSA)

Abstract: The aim of this study was to evaluate the usefulness of EGFR mutation status in serum DNA as a means of predicting a benefit from gefitinib (IRESSA) therapy in Japanese patients with non-small cell lung cancer (NSCLC). We obtained pairs of tumour and serum samples from 42 patients treated with gefitinib. EGFR mutation status was determined by a direct sequencing method and by Scorpion Amplification Refractory Mutation System (ARMS) technology. EGFR mutations were detected in the tumour samples of eight patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
167
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(186 citation statements)
references
References 32 publications
16
167
1
2
Order By: Relevance
“…Kimura et al (2006Kimura et al ( , 2007 reported the ability to detect EGFR mutations in serum samples of patients with advanced NSCLC with approximately 75% sensitivity. More recently, Maheswaran et al (2008) reported 92% sensitivity in the detection of EGFR mutations in isolated circulating tumor cells, including the detection of the T790M-resistant mutants in patients undergoing TKI therapy.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…Kimura et al (2006Kimura et al ( , 2007 reported the ability to detect EGFR mutations in serum samples of patients with advanced NSCLC with approximately 75% sensitivity. More recently, Maheswaran et al (2008) reported 92% sensitivity in the detection of EGFR mutations in isolated circulating tumor cells, including the detection of the T790M-resistant mutants in patients undergoing TKI therapy.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) The study included any reports based on the method of DNA isolation from fresh tissue or paraffin-embedded tissue, and the technique used to enhance tumor-derived DNA, which included either microdissection or use of the more sensitive polymerase chain reaction (PCR) amplification techniques. Not all consecutive NSCLC patients were included in the EGFR mutation analysis in every study.…”
Section: Methodsmentioning
confidence: 99%
“…This can be extracted from plasma and serum, providing an opportunity to develop a less-invasive and more accessible source of tumour DNA for mutation detection. Previous studies have demonstrated the feasibility of detecting tumour-specific mutations in cfDNA from patients with cancer, including detection of epidermal growth factor receptor mutations in patients with non-small-cell lung cancer (Kimura et al, 2006(Kimura et al, , 2007 and KRAS mutations in patients with pancreatic and colorectal cancers (Sorenson, 2000). More recently, BRAF mutations have been detected in cfDNA of patients with melanoma (Daniotti et al, 2007;Shinozaki et al, 2007;Yancovitz et al, 2007).…”
mentioning
confidence: 99%